The effect of religiosity on individual’s risk attitudes among young adults: The case of Christianity - Foo-Kune, Anthony (2013)
The Relationship between religiosity and individual risk preferences has long been a controversial topic. Using data collected from a questionnaire on 230 respondents, we argued that religiosity, in the case of Christianity, was a determinant of individual risk preferences and behaviours since it shaped relevant values and norms. We also argued that the degree of risk attitude was different according to the religious affiliation of the respondents. Targeting only individuals within the same range of age (20-25 years old) and controlling the gender factor, we have first found that there was a significant difference, in terms of risk preferences, between Protestants, Catholics and Orthodoxies, with Protestants being the most risk averse and Orthodoxies being the most risk taker. Also, our findings suggested that religiosity did have an impact on individual risk preferences. Secondly, we have provided evidences that mitigate the assumption that religious people were usually risk averse. In term of religious behaviours, our results did not support the relationship between religiosity and risk behaviours. Besides, there was hardly any difference in the degree of risk behaviour between the three denominations; only Protestants seemed to be significantly different from the others.